The future of domestic capital markets in developing countries - Litan, Robert E., 1950-; Pomerleano, Michael; Sundararajan, Vasudevan (Brookings Institution Press, 2003)
This volume brings together financial sector experts and leaders from around the world to provide practical guidance on strategies such as nuturing issuers, improving rules and institutions, addressing regulatory challenges and sequencing reforms.
Keywords: Capital market -- Developing countries.; Capital market -- Government policy -- Developing countries.; Capital market -- Law and legislation -- Developing countries.; BUSINESS & ECONOMICS -- Finance.; BUSINESS & ECONOMICS -- Development -- Economic Development.; Capital market; Capital market -- Government policy; Capital market -- Law and legislation; Developing countries